A sodium-intercalated composite hydroxide and a secondary battery cathode material

By preparing sodium-intercalated composite hydroxides using a tubular reactor and mixing them with a lithium or sodium source, the problems of complex sodium intercalation reactions and insufficient material stability in existing technologies are solved, enabling the efficient preparation of high-performance secondary battery cathode materials.

CN117142531BActive Publication Date: 2026-02-06XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311083947.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2026-02-06
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

Existing technologies for preparing sodium-intercalated composite hydroxides suffer from complex reactions, low efficiency, and insufficient material stability, especially poor cycling performance under high voltage.

Method used

A wet liquid-phase reaction was carried out using a tubular reactor to prepare a hydroxide precursor through a co-precipitation crystallization reaction. The precursor was then reacted with a sodium metal solution in the tubular reactor to form a sodium-intercalated composite hydroxide. Subsequently, it was mixed with a lithium source or a sodium source and subjected to heat treatment to form a secondary battery cathode material.

Benefits of technology

It improves the utilization rate of sodium metal and the uniform distribution of dopant elements, enhances the stability and cycle performance of the material, makes it suitable for high-voltage charge and discharge, and improves the capacity retention performance of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117142531B_ABST
    Figure CN117142531B_ABST
Patent Text Reader

Abstract

The application relates to a sodium-intercalated composite hydroxide and a secondary battery positive electrode material, and a sodium composite hydroxide preparation method which comprises the following steps: S1, mixing water, a complexing agent, a precipitant, an optional additive and a mixed metal solution to perform a coprecipitation crystallization reaction, performing solid-liquid separation after the reaction, and obtaining a hydroxide precursor; S2, adding the hydroxide precursor obtained in S1, a sodium metal solution and an oxidizing agent into a pipeline reactor, wherein the molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:(0.5-5), the reaction temperature in the pipeline reactor is controlled to be 110-300 DEG C, the reaction pressure is 1.0-10 MPa, the continuous reaction is performed for 0.5-20 hours, the pipeline reactor is discharged after the continuous reaction, the solid-liquid separation is performed on the obtained material liquid, the solid phase is obtained, the solid phase is dried, and a sodium-intercalated composite hydroxide is obtained. The sodium-intercalated composite hydroxide is subjected to heat treatment to form a solid solution, is further calcined to form a secondary battery positive electrode material, and the uniformity, stability and cycle performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a preparation technology of a secondary battery positive electrode material, in particular to a sodium-embedded composite hydroxide and a secondary battery positive electrode material. BACKGROUND

[0002] The positive oxide of a lithium ion battery is a mixed ion and electron conductor, has a large lithium storage and release capacity, and has been gradually expanded from the initial lithium cobaltate to ternary lithium ion batteries, lithium iron phosphate and other positive oxides. A new generation of high-voltage lithium ion batteries has a single charging cutoff voltage higher than 4.2 V, and is a representative of high-energy batteries, such as lithium-rich manganese-based oxides, high-voltage lithium cobaltate, nickel-rich positive oxides and the like. Since the material is charged and discharged at a high voltage, the internal structure is easily changed, and therefore, the high-voltage lithium ion battery has a high requirement for the stability of the material to ensure the cycle stability in the charging and discharging process.

[0003] On the other hand, doping the positive oxide to form a composite oxide can improve certain performance of the battery, but in a high-voltage lithium ion battery, the requirement for the doping conditions is extremely high, because once the doping is uneven, the battery performance will be greatly reduced at a high voltage, and the service life of the material will be reduced.

[0004] The layered oxide positive material of a sodium ion battery also has a similar situation. At present, the existing technology can improve the specific capacity and the first charge-discharge efficiency of the battery material by forming a solid solution structure through a sodium-embedding reaction, but the sodium-embedding reaction process is relatively complex and needs to use a strong oxidizing agent for two oxidation processes. For example, patent application CN 116282200A discloses a preparation method of a sodium-embedded cobalt-manganese composite oxide, which comprises the following steps: S1, obtaining a cobalt-manganese metal compound precursor; S2, adding the precursor, a sodium metal compound, water, an additive and an oxidizing agent into a reactor for reaction; S3, controlling the concentration of sodium ions in the reactor to be 3-12 mol / L, the reaction temperature to be 20-90 DEG C and the reaction time to be 3-60 h; S4, adding a strong oxidizing agent to the reaction material obtained in S3, and controlling the reaction conditions to embed sodium ions into the cobalt-manganese composite hydroxide structure to obtain a sodium-embedded cobalt-manganese composite hydroxide; and S5, performing solid-liquid separation on the reaction material obtained in S4, collecting the solid phase and performing heat treatment to obtain a sodium-embedded cobalt-manganese composite oxide. In the above process, two oxidation processes are performed in steps S2 and S3 to form the sodium-embedded hydroxide, which is not conducive to improving the production efficiency in industry; in addition, the cycle performance of the battery material obtained by adding a lithium source to the sodium-embedded cobalt-manganese composite oxide and then performing calcination still needs to be improved. SUMMARY

[0005] The present application aims to overcome the deficiencies in the prior art, and provides a sodium-intercalated composite hydroxide, which can be used as a precursor, and after further adding a lithium source or a sodium source, is calcined to form a corresponding secondary battery positive electrode material, and exhibits excellent capacity retention performance in high-voltage charging and discharging tests at room temperature.

[0006] Specific schemes are as follows:

[0007] A preparation method of a sodium-intercalated composite hydroxide, comprising the following steps:

[0008] S1, mixing water, a complexing agent, a precipitating agent, an optional additive, and a mixed metal solution to perform a coprecipitation crystallization reaction, and after the reaction is completed, performing solid-liquid separation to obtain a hydroxide precursor;

[0009] S2, adding the hydroxide precursor obtained in S1, a sodium metal solution, and an oxidizing agent into a pipeline reactor, wherein the molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:

[0010] (0.5-5),

[0011] The pipeline reactor comprises a base and a tubular reactor body fixedly arranged on the base, the tubular reactor body comprises a slurry tank, the outlet of the slurry tank is connected with the inlet of a feed pump, the outlet of the feed pump is in communication with a pipeline reaction cavity, the pipeline reaction cavity comprises at least one reaction tube, the length-diameter ratio of the reaction tube is greater than or equal to 10, and the end of the reaction tube is connected with a discharge tank.

[0012] The reaction temperature in the pipeline reactor is controlled to be 110-300 DEG C, the reaction pressure is 1.0-10 MPa, and after continuous reaction for 0.5-20 h, the pipeline reactor is discharged into the discharge tank, the obtained slurry is subjected to solid-liquid separation to obtain a solid phase, and the solid phase is dried to obtain the sodium-intercalated composite hydroxide.

[0013] Further, the complexing agent in S1 is at least one of ammonia, disodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chloride, and ammonium sulfate;

[0014] Preferably, the precipitating agent is at least one of sodium hydroxide, potassium hydroxide, and sodium carbonate;

[0015] Preferably, the additive is at least one of titanium, aluminum, magnesium, zirconium, tungsten, yttrium, strontium, niobium, and molybdenum metal compounds;

[0016] Preferably, the mixed metal solution contains at least one of nickel, iron, cobalt, manganese, and copper elements.

[0017] Further, the ammonia concentration in the coprecipitation crystallization reaction in S1 is 5-10 g / L, and is preferably 7 g / L.

[0018] Preferably, the pH of the co-precipitation crystallization reaction is 8-12, preferably 9-11.

[0019] Preferably, the temperature of the co-precipitation crystallization reaction is 40-80℃, preferably 50-70℃.

[0020] Further, the sodium metal solution in S2 is at least one of sodium hydroxide, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate, preferably at least one of sodium hydroxide, sodium sulfate, and sodium carbonate.

[0021] Preferably, the molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:(0.5-5), preferably 10:(1-4), and more preferably 10:(2-3).

[0022] Preferably, the oxidizing agent is at least one of oxygen, sodium chlorate, hydrogen peroxide, potassium permanganate, and nitric acid; and the molar ratio of the hydroxide precursor to the oxidizing agent is 10:(4-50), preferably 10:(10-40), and more preferably 10:(15-30).

[0023] Preferably, in the pipe-type reactor, the pipe-type reaction cavity contains 2-10 reaction pipes, and the reaction pipes are connected in series in a U shape. Preferably, the diameter of the reaction pipe is 1-10 cm.

[0024] Preferably, the reaction temperature in the pipe-type reactor is 120-280℃, preferably 150-200℃.

[0025] Preferably, the reaction pressure in the pipe-type reactor is 1.0-10 MPa, preferably 2.0-5.0 MPa.

[0026] Preferably, the reaction time of the pipe-type reactor is 1-10 h, preferably 2-8 h.

[0027] Preferably, the temperature for drying the solid phase is 50-200℃, preferably 80-150℃, and the drying time is 5-50 h, preferably 10-30 h.

[0028] The application also protects the intercalated sodium composite hydroxide prepared by the method for preparing the intercalated sodium composite hydroxide.

[0029] The application also protects a secondary battery positive electrode material, which is prepared by subjecting the intercalated sodium composite hydroxide to a first heat treatment, and then mixing the obtained product with a lithium source or a sodium source and subjecting to a second heat treatment to obtain the secondary battery positive electrode material.

[0030] Further, the temperature of the first heat treatment is 100-1000℃, preferably 400-800℃; the heat treatment time is 3-50h, preferably 5-20h, to obtain the sodium-embedded solid solution.

[0031] Further, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxide;

[0032] Preferably, the sodium source is selected from one or more of sodium hydroxide, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, sodium carbonate, sodium oxide;

[0033] The amount of the lithium source or the sodium source is added according to the target chemical formula, i.e., the chemical formula of the secondary battery cathode material is Li x Na y (Na z Me)O2, wherein 0≤x≤1.1, 0≤y≤1.1, 0≤x+y≤1.1, and 0

[0034] Further, preferably, the temperature of the second heat treatment is 300-1200℃, preferably 500-1000℃; preferably, the time of the second heat treatment is 10-50h, preferably 15-30h, and the atmosphere of the second heat treatment is air or oxygen.

[0035] The application also protects a battery comprising the secondary battery cathode material.

[0036] Advantages:

[0037] In the application, the sodium-embedded composite hydroxide is realized by using a pipeline type microreactor for wet liquid phase reaction, has a Na2O·Me2O3 solid solution structure, wherein Me is at least one metal element selected from nickel, iron, cobalt, manganese and copper, and the use of the pipeline type reactor as a reaction device can ensure stable product quality, improve the utilization rate of sodium metal, has a short reaction time, high degree of continuity and automation, and has a good industrial application prospect.

[0038] Further, the obtained sodium-embedded composite hydroxide is used as a precursor, mixed with a lithium source or a sodium source, and calcined to obtain a sodium-embedded lithium ion or sodium ion battery cathode material, which has obvious improvement in cycle performance and is beneficial to the preparation of high-performance energy storage batteries.

[0039] In addition, the method provided by the application can realize uniform distribution of the doping elements in the doped main body, and the material has good uniformity and exhibits good cycle performance in high-voltage charge and discharge tests. BRIEF DESCRIPTION OF DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the present application, the drawings will be briefly introduced as follows. Obviously, the drawings described in the following description are only some embodiments of the present application and not a limitation of the present application.

[0041] Figure 1 is a schematic diagram of a pipe reactor structure provided by an embodiment of the present application;

[0042] Figure 2 is a SEM image of a hydroxide precursor provided by an embodiment of the present application;

[0043] Figure 3 is a SEM image of a positive electrode material provided by an embodiment of the present application;

[0044] Figure 4 is a battery charge-discharge cycle performance diagram provided by an embodiment of the present application. DETAILED DESCRIPTION

[0045] The preferred embodiments of the present application will be described in more detail below. Although the preferred embodiments of the present application are described below, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. If no specific technology or condition is specified in the examples, the technology or condition described in the literature in the art or according to the product manual is used. If no manufacturer of the reagent or instrument is specified, it is a conventional product that can be obtained by purchase. In the following examples, unless otherwise specified, "%" means weight percent, and "parts" means weight parts.

[0046] Example 1

[0047] A pipe reactor, as shown in Figure 1 , includes a base and a pipe reactor body fixedly arranged on the base, the pipe reactor body includes a slurry tank, the outlet of the slurry tank is connected to the inlet of a feed pump, the outlet of the feed pump is in communication with a pipe reactor cavity, the pipe reactor cavity includes 4 U-shaped reaction tubes connected in series, the aspect ratio of each reaction tube is greater than or equal to 10, and the diameter of each reaction tube is 5 cm. The last reaction tube is connected to a discharge tank.

[0048] In other embodiments, the pipe reactor can also include 1 reaction tube, 2 or 3 or 5 reaction tubes, which can be selected according to the amount of reactant and the reaction time.

[0049] The above-mentioned pipe reactor is a continuous operation reactor, which is horizontally installed. The pipe reactor has good heat transfer and mass transfer capacity, can realize instantaneous uniform mixing of materials and efficient heat transfer, can be single pipe or multiple pipes in series, and has high efficiency of continuous operation, stable and controllable product, low cost and good effect.

[0050] Example 2

[0051] A cathode material was prepared by using the pipeline reactor in Example 1, and the main steps were as follows:

[0052] S1, water, ammonia, sodium hydroxide, zirconium sulfate, nickel sulfate, manganese sulfate were mixed, the concentration of ammonia was controlled to be 5 g / L, the pH of the solution was 11.00, the stirring intensity was 0.9 kw / m 2 h, the temperature was 50℃, the molar ratio of nickel sulfate to manganese sulfate was nickel:manganese = 0.49:0.5, and the coprecipitation crystallization reaction was carried out for 100 hours, and the hydroxide precursor was obtained after solid-liquid separation.

[0053] It was detected that the morphology of the hydroxide precursor was spherical, as shown in Figure 2 , the diameter of a single sphere was about 2-5um, which was ellipsoidal or spherical, and the surface of the sphere had a dense porous structure, and the gap between the spheres was clear.

[0054] S2, the hydroxide precursor obtained in S1 was added to the pipeline reactor with sodium acetate solution and hydrogen peroxide according to the molar ratio of 10:1.5:16, the reaction temperature of the pipeline reactor was controlled at 180℃, the reaction pressure was 3.5MPa, and the pipeline reactor was discharged after continuous reaction for 4h, the solid-liquid separation was carried out on the obtained liquid, and the solid phase was dried at 120℃ for 24h to obtain sodium-embedded composite hydroxide.

[0055] S3, the obtained sodium-embedded composite hydroxide was heat treated at a temperature of 500℃ for 10h, and then lithium source lithium hydroxide was further added according to the formula design, and then the obtained product was calcined at 850℃ for 12h in air atmosphere to obtain Li 0.83 Na 0.17 Ni 0.49 Mn 0.5 Zr 0.01 O2 cathode material, which is recorded as SN1.

[0056] The scanning electron microscope of SN1 showed that it was a single crystal product, as shown in Figure 3 , the surface of the single crystal particle was smooth, the crystallinity was good, and the average particle size was 0.5-10um, which indicated that the original single sphere morphology of the hydroxide precursor changed greatly after multiple heat treatments and addition of lithium source, and a stable composite oxide structure was formed.

[0057] Example 3

[0058] A cathode material was prepared by using the pipeline reactor in Example 1, and the main steps were as follows:

[0059] S1, water, ammonia, sodium hydroxide, nickel sulfate, ferric chloride, copper sulfate are mixed, the concentration of ammonia is controlled to be 7 g / L, pH is 10.80, and stirring intensity is 0.8 kw / m 2 ·h, the temperature is 60℃, the molar ratio of nickel sulfate, ferric chloride and copper sulfate is nickel: iron: copper = 0.35: 0.30: 0.35, and the coprecipitation crystallization reaction is performed for 80 hours, and the hydroxide precursor is obtained after solid-liquid separation, the hydroxide precursor has a spherical shape, the diameter of a single sphere is about 2-5um, is an ellipsoid or a spherical shape, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0060] S2, the hydroxide precursor obtained in S1 is added to a pipeline reactor with sodium hydroxide and hydrogen peroxide according to a molar ratio of 10:2:20 to perform sodium intercalation reaction, the reaction temperature is controlled to be 220℃, the reaction pressure is 2.0 MPa, and after continuous reaction for 5h, the pipeline reactor is discharged, the solid phase is obtained after solid-liquid separation of the obtained liquid, and the solid phase is dried at a temperature of 130℃ for 24h to obtain sodium intercalated composite hydroxide.

[0061] S3, the obtained sodium intercalated composite hydroxide is heat treated at a temperature of 650℃ for 8h, and according to the formula design, sodium source sodium hydroxide is further added, and then the obtained product is calcined at 980℃ for 10h in an air atmosphere to obtain Na 1.03 Ni 0.35 Fe 0.3 Cu 0.35 O2 positive electrode material, which is recorded as SN2, and the scanning electron microscope of SN2 shows that it is a single crystal product.

[0062] Example 4

[0063] The pipeline reactor in Example 1 is used to prepare a positive electrode material, and the main steps are as follows:

[0064] S1, water, ethylenediaminetetraacetic acid disodium, sodium hydroxide, manganese sulfate, ferric chloride, copper sulfate are mixed, the concentration of ethylenediaminetetraacetic acid disodium is controlled to be 7 g / L, pH is 9.50, and stirring intensity is 0.8 kw / m 2 ·h, the temperature is 70℃, the molar ratio of manganese sulfate, ferric chloride and copper sulfate is manganese: iron: copper = 0.35: 0.30: 0.35, and the coprecipitation crystallization reaction is performed for 80 hours, and the hydroxide precursor is obtained after solid-liquid separation, the hydroxide precursor has a spherical shape, the diameter of a single sphere is about 2-5um, is an ellipsoid or a spherical shape, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0065] S2, the hydroxide precursor obtained in S1 is added into a pipeline reactor with sodium hydroxide and hydrogen peroxide according to a molar ratio of 10:3:30 to perform sodium intercalation reaction, the reaction temperature is controlled at 150 DEG C, the reaction pressure is 3.0 MPa, the pipeline reactor is discharged after continuous reaction for 5 h, the solid phase is obtained by solid-liquid separation of the obtained liquid, and the solid phase is dried at a temperature of 130 DEG C for 24 h to obtain sodium-intercalated composite hydroxide.

[0066] S3, the obtained sodium-intercalated composite hydroxide is heat treated at a temperature of 750 DEG C for 6 h, sodium source sodium hydroxide is further added according to the formula design, and then the obtained product is calcined at 1000 DEG C for 10 h in an air atmosphere to obtain Na 1.03 Mn 0.35 Fe 0.3 Cu 0.35 O2 positive electrode material, and scanning electron microscopy shows that it is a single crystal product.

[0067] Example 5

[0068] The pipeline reactor in Example 1 is used to prepare a positive electrode material, and the main steps are as follows:

[0069] S1, water, ammonium chloride, sodium hydroxide, nickel sulfate, ferric chloride and copper sulfate are mixed, the concentration of ammonium chloride is controlled to be 8 g / L, the pH is 11.50, the stirring intensity is 0.5 kw / m 2 ·h, the temperature is 50 DEG C, and the molar ratio of nickel sulfate, ferric chloride and copper sulfate is nickel: iron: copper = 0.35: 0.30: 0.35, and the co-precipitation and crystallization reaction is performed for 80 hours, and the hydroxide precursor is obtained by solid-liquid separation, the morphology of the hydroxide precursor is spherical, the diameter of a single sphere is about 2-5 um, and the sphere is ellipsoidal or spherical, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0070] S2, the hydroxide precursor obtained in S1 is added into a pipeline reactor with sodium hydroxide and hydrogen peroxide according to a molar ratio of 10:3:30 to perform sodium intercalation reaction, the reaction temperature is controlled at 150 DEG C, the reaction pressure is 3.0 MPa, the pipeline reactor is discharged after continuous reaction for 5 h, the solid phase is obtained by solid-liquid separation of the obtained liquid, and the solid phase is dried at a temperature of 130 DEG C for 24 h to obtain sodium-intercalated composite hydroxide.

[0071] S3, the obtained sodium-intercalated composite hydroxide is heat treated at a temperature of 750 DEG C for 6 h, sodium source sodium hydroxide is further added according to the formula design, and then the obtained product is calcined at 1000 DEG C for 10 h in an air atmosphere to obtain Na 1.03 Ni 0.35 Fe 0.3 Mn 0.35O2 cathode material, scanning electron microscopy shows that it is a single crystal product.

[0072] Example 6

[0073] The main steps are as follows:

[0074] S1, water, ammonium nitrate, potassium hydroxide, nickel sulfate, cobalt trichloride, manganese sulfate are mixed, the concentration of ammonium nitrate is controlled to be 7 g / L, the pH is 9.50, and the stirring intensity is 0.8 kw / m 2 h, the temperature is 70℃, the molar ratio of nickel sulfate, cobalt trichloride and manganese sulfate is nickel:iron:copper=0.35:0.30:0.35, and the coprecipitation crystallization reaction is carried out for 80 hours, and the hydroxide precursor is obtained by solid-liquid separation, the hydroxide precursor is spherical in shape, the diameter of a single sphere is about 2-5um, and the sphere is ellipsoidal or spherical, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0075] S2, the hydroxide precursor obtained in S1 is added to the pipeline reactor with sodium hydroxide and hydrogen peroxide according to the molar ratio of 10:1:30 to carry out sodium intercalation reaction, the reaction temperature is controlled at 120℃, the reaction pressure is 5.0MPa, and the continuous reaction is carried out for 8h, then the pipeline reactor is discharged, the solid-liquid separation is carried out on the obtained liquid, and the solid phase is obtained, and the obtained solid phase is dried at 130℃ for 24h to obtain sodium intercalated composite hydroxide.

[0076] S3, the obtained sodium intercalated composite hydroxide is heat treated at a temperature of 700℃ for 8h, and then according to the formula design, sodium source sodium hydroxide is further added, and then the obtained product is calcined at 980℃ for 10h in air atmosphere to obtain Na 1.03 Ni 0.35 Co 0.3 Mn 0.35 O2 cathode material, scanning electron microscopy shows that it is a single crystal product.

[0077] Example 7

[0078] The main steps are as follows:

[0079] S1, water, ammonia, sodium carbonate, nickel sulfate, ferric trichloride, copper sulfate are mixed, the concentration of ammonia is controlled to be 10 g / L, the pH is 12.0, and the stirring intensity is 0.8 kw / m 2• h, temperature is 60℃, the molar ratio of nickel sulfate, ferric chloride, copper sulfate is nickel: iron: copper = 0.35: 0.30: 0.35, and a coprecipitation crystallization reaction is performed for 80 hours, and a hydroxide precursor is obtained after solid-liquid separation, the hydroxide precursor has a spherical shape, the diameter of a single sphere is about 2-5um, and the sphere has an ellipsoid or spherical shape, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0080] S2, the hydroxide precursor obtained in S1 is added into a pipeline reactor with sodium hydroxide and hydrogen peroxide according to a molar ratio of 10:4:30 to perform a sodium intercalation reaction, the reaction temperature is controlled at 280℃, the reaction pressure is 1.0MPa, and after continuous reaction for 5h, the pipeline reactor is discharged, the solid phase is obtained after solid-liquid separation of the obtained liquid, and the obtained solid phase is dried at a temperature of 130℃ for 24h to obtain a sodium intercalated composite hydroxide.

[0081] S3, the obtained sodium intercalated composite hydroxide is heat treated at a temperature of 650℃ for 8h, and according to the needs of formula design, sodium source sodium hydroxide is further added, and then the obtained product is calcined at 980℃ for 10h in an air atmosphere to obtain a Na 1.03 Ni 0.35 Fe 0.3 Cu 0.35 O2 cathode material, and scanning electron microscopy shows that it is a single crystal product.

[0082] Example 8

[0083] The pipeline reactor in Example 1 is used to prepare a cathode material, and the main steps are as follows:

[0084] S1, water, ammonia, sodium hydroxide, nickel sulfate, ferric chloride, and copper sulfate are mixed, the ammonia concentration is controlled at 5g / L, the pH is 8, and the stirring intensity is 0.8kw / m 2 • h, temperature is 60℃, the molar ratio of nickel sulfate, ferric chloride, copper sulfate is nickel: iron: copper = 0.35: 0.30: 0.35, and a coprecipitation crystallization reaction is performed for 80 hours, and a hydroxide precursor is obtained after solid-liquid separation, the hydroxide precursor has a spherical shape, the diameter of a single sphere is about 2-5um, and the sphere has an ellipsoid or spherical shape, the surface of the sphere has a dense porous structure, and the gap between the spheres is clear.

[0085] S2, the hydroxide precursor obtained in S1 is added into a pipeline reactor with sodium hydroxide and hydrogen peroxide according to a molar ratio of 10:2:20 to perform a sodium intercalation reaction, the reaction temperature is controlled at 200℃, the reaction pressure is 2.0MPa, and after continuous reaction for 5h, the pipeline reactor is discharged, the solid phase is obtained after solid-liquid separation of the obtained liquid, and the obtained solid phase is dried at a temperature of 130℃ for 24h to obtain a sodium intercalated composite hydroxide.

[0086] S3, the obtained sodium-intercalated composite hydroxide was heat treated at a temperature of 650°C for 8h, and then sodium hydroxide was further added according to the formula design, and then the obtained product was calcined at 980°C for 10h in an air atmosphere to obtain Na 1.03 Ni 0.35 Fe 0.3 Cu 0.35 O2positive electrode material, and the scanning electron microscope showed that it was a single crystal product.

[0087] Comparative Example 1

[0088] The present comparative example was similar to Example 2, except that the molar ratio of the hydroxide precursor controlled in S2 to sodium acetate solution and hydrogen peroxide was 10:0.3:16, and it was found that the scanning electron microscope of the obtained sodium-intercalated metal hydroxide was quite different from that of Example 2.

[0089] The sodium-intercalated metal hydroxide was heat treated according to the method of S3 in Example 2 at a temperature of 500°C for 10h, and then lithium hydroxide was further added according to the formula design, and then the obtained product was calcined at 850°C for 12h in an air atmosphere to obtain a material recorded as DN1.

[0090] Comparative Example 2

[0091] The present comparative example was similar to Example 3, except that the reaction pressure of the pipeline reactor controlled in S2 was 0.5MPA, and the reaction temperature was 100°C, and it was found that the scanning electron microscope of the obtained sodium-intercalated metal hydroxide was quite different from that of Example 1.

[0092] The sodium-intercalated metal hydroxide was heat treated according to the method of S3 in Example 3 at a temperature of 650°C for 8h, and then sodium hydroxide was further added according to the formula design, and then the obtained product was calcined at 980°C for 10h in an air atmosphere to obtain a material recorded as DN2.

[0093] Comparative Example 3

[0094] The present comparative example was similar to Example 2, except that a pipeline reactor was not used in S2, but a cylindrical high-pressure reaction kettle with a volume of 3L was used. The other steps were the same as those of Example 2, and the obtained material was recorded as DN3.

[0095] Comparative Example 4

[0096] The present comparative example was similar to Example 2, except that zirconium sulfate was not added in S1. The other steps were the same as those of Example 2, and the obtained material Li 0.83 Na 0.17 Ni 0.49 Mn 0.5 O2was recorded as DN4.

[0097] Performance detection

[0098] The positive electrode material prepared in the examples and comparative examples is prepared into a battery in the following manner:

[0099] The positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) are dissolved in NMP solvent under vacuum condition to prepare a positive electrode slurry with a solid content of 70 wt% at a mass ratio of 80:10:10. The positive electrode slurry is coated on a current collector aluminum foil, dried at 120°C under vacuum for 12h, punched, and a positive electrode round sheet with a diameter of 19mm is prepared. The graphite, CMC and SBR are dissolved in deionized water under vacuum condition to prepare a negative electrode slurry with a solid content of 40 wt% at a mass ratio of 90:5:5. The negative electrode slurry is coated on a current collector copper foil, dried at 100°C under vacuum for 12h, punched, and a negative electrode round sheet with a diameter of 19mm is prepared, with a negative electrode capacity: positive electrode capacity = 1.1:1.

[0100] The battery is assembled in an argon-filled glove box, and the assembly sequence is positive shell-positive sheet-separator-negative sheet-stainless steel sheet-spring sheet-negative shell. The electrolyte is 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC) added, and the separator is a polypropylene microporous membrane.

[0101] The assembled battery is subjected to charge-discharge test, as shown in Figure 4 The capacity retention rate of the battery prepared in Example 2 is better than that of Comparative Example 1 at 0.5C rate in the charge-discharge interval of 3.0-4.4V at room temperature, as shown in Table 1.

[0102] Table 1 Battery charge-discharge performance table

[0103]

[0104] The above describes the preferred embodiments of the present application, but the present application is not limited to the specific details in the above-described embodiments. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, and these simple modifications all belong to the protection scope of the present application.

[0105] In addition, it should be noted that each specific technical feature described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present application will not further describe various possible combinations.

[0106] In addition, various different embodiments of the present application can also be combined in any appropriate manner, as long as it does not deviate from the idea of the present application, and it should be considered as disclosed by the present application.

Claims

1. A method for preparing a sodium-intercalated complex hydroxide, characterized in that: Includes the following steps: S1. Water, a complexing agent, a precipitant, and optional additives are mixed with a mixed metal solution to carry out a co-precipitation crystallization reaction. After the reaction, solid-liquid separation is performed to obtain a hydroxide precursor. The complexing agent is at least one of ammonia, disodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chloride, and ammonium sulfate. The precipitant is at least one of sodium hydroxide, potassium hydroxide, and sodium carbonate. The mixed metal solution contains at least one of nickel, iron, cobalt, manganese, and copper. The ammonia concentration in the co-precipitation crystallization reaction is 5-10 g / L. The temperature of the co-precipitation crystallization reaction is 40-80℃. S2. The hydroxide precursor obtained in S1, sodium metal solution, and oxidant are added to a tubular reactor, wherein the molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:(0.5-5). The tubular reactor includes a base and a tubular reactor body fixedly mounted on the base. The tubular reactor body includes a slurry tank, the outlet of which is connected to the inlet of a feed pump, and the outlet of the feed pump is connected to a tubular reaction chamber. The tubular reaction chamber includes at least one reaction tube with a length-to-diameter ratio greater than or equal to 10. The end of the reaction tube is connected to a discharge tank. The reaction temperature in the pipeline reactor is controlled at 110-300℃ and the reaction pressure is 1.0-10MPa. After continuous reaction for 0.5-20h, the pipeline reactor is discharged to the discharge tank. The resulting liquid is separated into solid and liquid phases, and the solid phase is dried to obtain sodium-intercalated composite hydroxide. The additive in S1 is at least one of titanium, aluminum, magnesium, zirconium, tungsten, yttrium, strontium, niobium, and molybdenum metal compounds.

2. The method for preparing the sodium-intercalated composite hydroxide according to claim 1, characterized in that: The ammonia concentration for the coprecipitation crystallization reaction described in S1 is 7 g / L.

3. The method for preparing the sodium-intercalated composite hydroxide according to claim 2, characterized in that: The pH of the coprecipitation crystallization reaction is 8-12.

4. The method for preparing the sodium-intercalated composite hydroxide according to claim 3, characterized in that: The pH of the coprecipitation crystallization reaction is 9-11.

5. The method for preparing the sodium-intercalated composite hydroxide according to claim 2, characterized in that: The temperature for the coprecipitation crystallization reaction is 50-70℃.

6. The method for preparing the sodium-intercalated composite hydroxide according to claim 1, characterized in that: The sodium metal solution mentioned in S2 is at least one of sodium hydroxide, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate.

7. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The sodium metal solution mentioned in S2 is at least one of sodium hydroxide, sodium sulfate, and sodium carbonate.

8. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:(1-4).

9. The method for preparing the sodium-intercalated composite hydroxide according to claim 8, characterized in that: The molar ratio of the hydroxide precursor to sodium ions in the sodium metal solution is 10:(2-3).

10. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The oxidant is selected from at least one of oxygen, sodium chlorate, hydrogen peroxide, potassium permanganate and nitric acid; the molar ratio of the hydroxide precursor to the oxidant is 10:(4-50).

11. The method for preparing the sodium-intercalated composite hydroxide according to claim 10, characterized in that: The molar ratio of the hydroxide precursor to the oxidant is 10:(10-40).

12. The method for preparing the sodium-intercalated composite hydroxide according to claim 11, characterized in that: The molar ratio of the hydroxide precursor to the oxidant is 10:(15-30).

13. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The tubular reactor contains 2-10 reaction tubes connected in series in a U-shape.

14. The method for preparing the sodium-intercalated composite hydroxide according to claim 13, characterized in that: The diameter of the reaction tube is 1-10 cm.

15. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The reaction temperature inside the pipeline reactor is 120-280℃.

16. The method for preparing the sodium-intercalated composite hydroxide according to claim 15, characterized in that: The reaction temperature inside the pipeline reactor is 150-200℃.

17. The method for preparing the sodium-intercalated complex hydroxide according to claim 6, characterized in that: The reaction pressure inside the pipeline reactor is 2.0-5.0 MPa.

18. The method for preparing the sodium-intercalated complex hydroxide according to claim 6, characterized in that: The reaction time of the pipeline reactor is 1-10 hours.

19. The method for preparing the sodium-intercalated composite hydroxide according to claim 18, characterized in that: The reaction time of the pipeline reactor is 2-8 hours.

20. The method for preparing the sodium-intercalated composite hydroxide according to claim 6, characterized in that: The solid phase is dried at a temperature of 50~200℃ for a time of 5~50h.

21. The method for preparing the sodium-intercalated composite hydroxide according to claim 20, characterized in that: The temperature for drying the solid phase is 80~150℃.

22. The method for preparing the sodium-intercalated composite hydroxide according to claim 20, characterized in that: The drying time for the solid phase is 10-30 hours.

23. The sodium-intercalated composite hydroxide prepared by the method according to any one of claims 1-22.

24. A secondary battery cathode material, characterized in that: The sodium-intercalated composite hydroxide of claim 23 is subjected to a first heat treatment, and the resulting product is mixed with a lithium source or a sodium source and then subjected to a second heat treatment to obtain the positive electrode material of the secondary battery.

25. The secondary battery cathode material according to claim 24, characterized in that: The temperature of the first heat treatment is 100~1000℃; the heat treatment time is 3~50h, to obtain a sodium-intercalated solid solution.

26. The secondary battery cathode material according to claim 25, characterized in that: The temperature of the first heat treatment is 400-800℃.

27. The secondary battery cathode material according to claim 25, characterized in that: The duration of the heat treatment is 5-20 hours.

28. The secondary battery cathode material according to claim 24, characterized in that: The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxide.

29. The secondary battery cathode material according to claim 28, characterized in that: The sodium source is selected from one or more of sodium hydroxide, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, sodium carbonate, and sodium oxide. The amount of lithium or sodium source added is based on the target chemical formula, i.e., the chemical formula of the secondary battery cathode material is Li. x Na y (Na z Me)O2, where 0≤x≤1.1, 0≤y≤1.1, 0≤x+y≤1.1, and 0<z≤0.

2.

30. The secondary battery cathode material according to claim 28, characterized in that: The temperature of the secondary heat treatment is 300~1200℃.

31. The secondary battery cathode material according to claim 30, characterized in that: The temperature of the secondary heat treatment is 500~1000℃.

32. The secondary battery cathode material according to claim 30, characterized in that: The duration of the secondary heat treatment is 10-50 hours, and the atmosphere for the secondary heat treatment is either air or oxygen.

33. The secondary battery cathode material according to claim 32, characterized in that: The duration of the secondary heat treatment is 15-30 hours.

34. A battery comprising the secondary battery positive electrode material according to any one of claims 24-33.

Citation Information

Patent Citations

  • Sodium-embedded cobalt-manganese composite oxide and sodium-embedded lithium ion battery positive electrode material

    CN116282200A

  • Methods for preparing nickel-cobalt-manganese ternary positive electrode material with large single crystal morphology and precursor thereof

    CN111943279A

  • Sodium-embedded metal compound and sodium ion battery positive electrode material

    CN116454268A